Tannic acid (TA): A molecular tool for chelating and imaging labile iron - Isara Phiwchai (2018)
© 2017 Elsevier B.V. This report presents the potential utilization of tannic acid (TA) as a natural iron chelator. TA is capable of binding with small ferric complexes without competitive binding with endogenous iron-containing molecules such as ferritin and transferrin. It was observed that the extracellular iron binding of TA resulted in the formation of self-assembled Fe 3 + -TA complexes, which were then taken up by HepG2 cells via phagocytosis pathway with autophagy-inducing properties. Obviously, TA was found to inhibit iron-induced HepG2 cell growth. However, cellular interactions and biological responses to the treatment were found to depend on availability of iron. Based on the results of the iron efflux experiment, it can be stated that TA has the capability to mobilize iron from cells in the form of assembled Fe 3 + -TA complexes. Interestingly, TA-mediated cellular iron influx and efflux were successfully monitored via MRI. The results of this study suggest that TA can be used as a molecular tool for chelating and imaging labile iron. This might be a promising approach for prevention and treatment of iron-associated cancer or other iron overload disorders.